Penggunaan molases pada silase kulit pisang nangka (Musa paradisiaca informa typica) terhadap kandungan serat kasar dan protein kasar - Rahmat Hidayat; Syifa Nurjannah; Hilman Permana (University of Insan Cendekia Mandiri, 2021)
The purpose of this research was to determine the used of molases as an additive in making banana jackfruit peel silage on crude fiber and crude protein. This research was conducted in Sirnaraja, Mandalasari village, Cikalongwetan district, West Bandung regency for 21 days, while the sample test carried out Balai Pengujian Mutu dan Keamanan Pakan/Bahan Pakan (BPMKP/BP) at the Cikole-Lembang. The method used was Completely Randomized Design (CRD), with four treatments (P0 : banana jackfruit peel silage with 0% molases), (P1 : banana jackfruit peel silage with 1% molases), (P2 : banana jackfruit peel silage with 3% molases), (P3 : banana jackfruit peel silage with 5% molases) and five replication. The data obtained were analyzed by ANOVA and Duncan’s multiple range test. The result show that the used of molases as an additive was significantly (P<0,05) of crude fiber and crude protein with average 8,79-31,61% and 8,79-9,55%. The used of 3% molases is the most optimal of the decrease crude fiber and increase crude protein.